Enabling Students to Learn Scientific Methods Through Spreadsheet - Fauzi, Ahmad (Sebelas Maret University, 2016)
Spreadsheet programs are enormously flexible, familiar, and relatively easy to use. Commonly, spreadsheets are used in business, technique, and education. Spreadsheets are widely used in various disciplines of education to simulate phenomena in order to solve problems. In traditional simulation using spreadsheet, the students asked to change certain parameters to visualize a mathematical relationship to get the concept. Consequently, students become passive in the learning process in classroom. Whereas, in science, the students just not only need to understand the concept, they also expected to know how to get the concept. It is argued in this paper that spreadsheets could also be used to enable students to learn scientific methods, including: the importance of model building, the relationships among variables in a model or models, and how to use a model to predict outcomes. By using a constructivist approach, students asked to make a supposition and test it using spreadsheet. The students could be required to investigate an open-ended problem with the help of hand out. Based on this research, it can be concluded that students motivated to participate in the class. Besides that, students can learn more in depth used scientific methods.